Evaluation of Serum Ferritin in Hospitalized Patients with COVID-19 as A Potential Biomarker for Assessing COVID-19 Severity - Naznin, Colonel Lubna; Giti, Susane; Ahmed Khan, Arif; Akter, Yasmin; Parvin, Mimi; Sultana, Sarmin (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Corona virus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), has become global pandemic. Proinûammatory mediator, serum ferritin is reported to be elevated significantly by different studies in COVID-19. Our study was aimed to find whether serum ferritin level can be employed as a biomarker to assess the disease severity in COVID-19 cases. Methods: This cross sectional observational study was carried out at Armed Forces Institute of Pathology (AFIP), a tertiary referral laboratory between 15 March 2020 and 15 June 2020. Total 2418 hospitalized RT-PCR confirmed COVID- 19 patients from Combined Military Hospital (CMH) were included in our study. Serum ferritin was measured by electrochemiluminescence immunoassay and was compared between the severe and non-severe groups. P-value < 0.05 was considered statistically significant. Results: Total patients were 2418, among them 337 (13.9%) from intensive care unit (ICU) and 2081 (86.1%) from non- ICU. Median age and IQR were 60.5 (51.5–68.0) years in ICU patients versus 38.0 (28-46.1) years in non-ICU patients (p <0.0001). Most (86.8%) patients were males; 82.8% in ICU and 87.5% in non-ICU. Serum ferritin was significantly higher (p<0.0001) in ICU patients; median and IQR was 952.8 (529.9 - 1520.5) ng/mL versus 254.2 (156.1 - 441.9) ng/mL (p <0.0001) in non-ICU patients. Serum ferritin, at cut off value (COV) <550 ng/mL had sensitivity 82.36% and specificity 73.59% for categorization of COVID-19 cases as non-severe. Comparison of proportions of ICU and non-ICU patients was found highly significant (p <0.0001 at 95% confidence interval) with this cut off value. Conclusions: Serum ferritin level was significantly high among COVID-19 patients requiring ICU admission than non-ICU cases. Serum ferritin may be used for categorizing COVID-19 patients. Cut off value 550 ng/mL can be meaningfully used for this categorization, above which should be considered severe and need more careful monitoring. J Bangladesh Coll Phys Surg 2021; 39: 220-224